Pharmacy Practice In Telehealth: Adapting To The Post-COVID-19 Era (Journal of Namibian Studies : History Politics Culture, 2023)
The COVID-19 pandemic catalyzed significant changes in healthcare delivery, leading to the rapid adoption of telehealth services across all medical fields, including pharmacy practice. Telepharmacy, the provision of pharmaceutical care via telecommunication, emerged as an essential service during the pandemic. This review explores how pharmacy practice has adapted to the post-COVID-19 era through telepharmacy, examining the challenges, benefits, and future applications of virtual patient care. As telepharmacy continues to evolve, it promises to expand access to healthcare, improve patient outcomes, and offer innovative ways to deliver pharmaceutical care. However, several barriers must be addressed, including regulatory limitations, technological access, and the need for training.